Risk factors for central venous catheter related bloodstream infection: a multicenter study of intensive care unit and haemodialysis unit (Bangladesh Medical Journal, 2019)
The clinical condition of the patient, type of central venous catheter (CVC), site and duration of CVC placement are the factors affecting the risk of infection. The aim of this study was to examine and find out the risk factors of CVC related blood stream infections (CVC-BSI). This cross sectional study was carried out in the Department of Microbiology and Immunology of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh during the period of July 2011 to June 2012. One hundred patients who were admitted in ICU of BSMMU and ICU and haemodialysis unit of Dhaka Medical College Hospital (DMCH) having central venous catheter, were enrolled in the study. The rate of CVC-BSI was 11% and the incidence was observed to be 11.14/1000 catheter days. Both CVC-BSI and CVC colonization were higher in trilumen than in bilumen central venous catheter. CVC-BSI rate was 12.79% in trilumen whereas there was no CVC-BSI in patient with bilumen catheter. The mean duration from CVC insertion to development of CVC-BSI was 14 days, CVC colonization was 8.41 days and noninfected CVC was 6 days. CVC-BSI and CVC colonization were most common in right femoral vein where CVC-BSI was 18.52% and CVC colonization was 59.26%, whereas no CVC-BSI was found in right internal jugular vein. Risk factors for CVC-BSI included type of CVC, site of CVC placement, duration of catheterization were not found statistically significant in this study. CVC-BSI and CVC colonization were higher in trilumen catheter and rate raised with increased duration of placement and highest number of CVC-BSI and colonization was found in right femoral vein.Bangladesh Med J. 2018 Jan; 47 (1): 18-21